Amoras sem espinhos : a recepção de Fábulas (1922), de Monteiro Lobato, por crianças do ensino fundamental - Silva, Adriana Paula dos Santos (2008)
This dissertation relates results from the analysis of the reception of literary texts by students that belong to the first cycle of a private primary school, situated in the city of Maringá - Paraná. The analyzed texts are twenty-two fables, from the homonym book, by the Brazilian writer Monteiro Lobato (1992-1948). Thus, the first part of the research deals with the resources of literary adaptation, translation and parody as tools used in the lobatiana rewriting, verifying their influence in the constitution of the narrative text. In relation to the reading universe, it was read and used as theoretical support, the structure and history of fable genre, in order to understand the readings presented by the readers of Monteiro Lobato, in the reading activity in the classroom.